Low Osteopontin N-Terminal Fragment and Carotid Plaque Stability Associated with Statin or Antiplatelet Therapy - Hamias, Rachel; Volvich, Liobov; Paran, Esther; Sion-Vardi, Neta; Novack, Victor; Szendro, Gabriel; Greenberg, George; Rudich, Assaf; Wolak, Talya (Current Vascular Pharmacology, 2016)
Introduction: Full-length osteopontin (OPN-FL), whose levels are elevated in association with atherosclerosis, is cleaved by thrombin, resulting in the formation of a putatively biologically-active N-terminal cleavage product (OPNN). This study addresses the hypothesis that statin and antiplatelet therapy in hypertensive patients specifically reduces OPN-N, rather than OPN-FL, in carotid plaques. Methods: Seventy-four carotid plaques were collected from patients who underwent carotid endarterectomy (CEA). Plaque tissue was used to measure OPN proteins and for histological and immunohistochemical characterization. Results: There were 22 statin-negative and 52 statin-treated patients. In the carotid plaque, immunohistochemical staining for macrophages was higher in statin-negative vs. statin-treated patients (high CD68 immunostaining was in 61.9 vs. 28.6%, p=.03, respectively). OPN-FL staining had a similar trend, but without statistical significance (78.7 vs. 47.8%, p=.08, respectively). Western blot analysis of plaque OPN-FL showed that statin treatment was not associated with significant alteration of its abundance, but with a significantly lower plaque content of OPN-N [median 0.08 (IQR 0.05-1.01) vs. 0.81 (IQR 0.27-2.86), respectively, p=.015]. Comparable pattern of association between OPN proteins and antiplatelet therapy was found: the abundance of OPN-FL was not different in plaques from untreated or treated patients, while the abundance of OPN-N was significantly reduced in antiplatelet treated vs. non-treated patients [0.08, (IQR 0.05-0.66) vs. 0.89, (IQR 0.13-1.94), p=0.004]. Conclusion: The effect of anti-atherosclerotic treatment on carotid plaques of hypertensive patients more readily associates with OPN-N than with OPN-FL expression, suggesting that anti-atherosclerotic treatment including statins and antiplatelet drugs modulates the
Keywords: Osteopontin